Sequential Paleotetraploidization shaped the carrot genome - Jinpeng Wang (BMC Plant Biology, 2020)
Abstract Background Carrot (Daucus carota subsp. carota L.) is an important root crop with an available high-quality genome. The carrot genome is thought to have undergone recursive paleo-polyploidization, but the extent, occurrences, and nature of these events are not clearly defined. Results Using a previously published comparative genomics pipeline, we reanalysed the carrot genome and characterized genomic fractionation, as well as gene loss and retention, after each of the two tetraploidization events and inferred a dominant and sensitive subgenome for each event. In particular, we found strong evidence of two sequential tetraploidization events, with one (Dc-α) approximately 46–52 million years ago (Mya) and the other (Dc-β) approximately 77–87 Mya, both likely allotetraploidization in nature. The Dc-β event was likely common to all Apiales plants, occurring around the divergence of Apiales-Bruniales and after the divergence of Apiales-Asterales, likely playing an important role in the derivation and divergence of Apiales species. Furthermore, we found that rounds of polyploidy events contributed to the expansion of gene families responsible for plastidial methylerythritol phosphate (MEP), the precursor of carotenoid accumulation, and shaped underlying regulatory pathways. The alignment of orthologous and paralogous genes related to different events of polyploidization and speciation constitutes a comparative genomics platform for studying Apiales, Asterales, and many other related species. Conclusions Hierarchical inference of homology revealed two tetraploidization events that shaped the carrot genome, which likely contributed to the successful establishment of Apiales plants and the expansion of MEP, upstream of the carotenoid accumulation pathway.